Testing the Transparency Benefits of Inflation Targeting : Evidence from Private Sector Forecasts - Crowe, Christopher (IMF Working Papers; Working Paper, 2006)
I test whether inflation targeting (IT) enhances transparency using inflation forecast data for 11 IT adoption countries. IT adoption promotes convergence in forecast errors, suggesting that it enhances transparency. This effect is robust to dropping observations, is strengthened by using instrumental variable estimation to eliminate mean-reversion, and is absent in placebo regressions (where IT adoption is shifted by a year). This result supports Morris and Shin's (2002) contention that better public information is most beneficial for forecasters with bad private information. However, it does not support their hypothesis that better public information could make private forecasts less accurate.